Nutritional Knowledge and Practice among Patients with Non-communicable Diseases Attending Mbale Regional Referral Hospital in Eastern Uganda: A Cross Sectional Study - Nambala, Esther; Byakika-Tusiime, Jayne; Gavamukulya, Yahaya (International Journal of TROPICAL DISEASE & Health, 2019)
To determine nutritional knowledge and practices among patients with Non-Communicable Diseases (NCD) attending Mbale Regional Referral hospital, in Eastern Uganda. Study Design: A mixed methods cross sectional study design was used. Place and Duration of Study: Mbale Regional Referral Hospital among patients attending the NCD clinic from May to July 2017. Methodology: Two hundred sixty clients were recruited for the study. Quantitative data was collected through structured administered questionnaires. Quantitative data was analyzed at univariate, bivariate and multivariate levels. Chi square test and logistic regression were used to determine the association between nutrition knowledge and utilization. Qualitative data was coded first and summarized according to the themes. Results: The mean age of the respondents was 55 years (SD= 14) and hospital was the main source of nutrition information (n=156, 60%). Most respondents (n=156, 60%) had a high level of nutrition knowledge, however only 48.8% (n=127) were utilizing the knowledge. Those who had attained secondary level of education were 2.308 more likely to utilize the nutrition knowledge than those who had never studied P value of .028, 95CI (1.093-4.874). Those with tertiary education were even 9.261 times more likely to utilize the knowledge P value <.001 95CI (2.721-31.522). Those with adequate knowledge were about 1.6 times most likely to utilize the nutrition knowledge compared to those with inadequate knowledge level, however, with the adjusted odd ratio of 1.573 at 95% CI (0.923- 2.868) the results were not statistically significant (P value .098). Conclusion: NCD patients had adequate knowledge, with a few of them utilizing the knowledge. High education level was associated with better nutrition practices.
Keywords: Non-communicable diseases; Nutritional knowledge; Diabetes mellitus; Hypertension